Does the Restoration Design and Material Affect Indirect Restorations' Marginal and Internal Gap, Interfacial Volume, and Fatigue Behavior? - Pereira, Gabriel Kalil Rocha; Pilecco, Rafaela Oliveira; da Rosa, Lucas Saldanha; Machry, Renan Vaz; Baldi, Andrea; Scotti, Nicola; Valandro, Luiz Felipe; Tribst, João Paulo Mendes; Kleverlaan, Cornelis Johannes (European Journal of Dentistry, 2025)
This article evaluates the marginal and internal gap, interfacial volume, and fatigue behavior in computer-aided design-computer-aided manufacturing (CAD-CAM) restorations with different designs (crowns or endocrowns) made from lithium disilicate-based ceramic (LD, IPS e.max CAD, Ivoclar AG) or resin composite (RC, Tetric CAD, Ivoclar AG).Simplified LD and RC crowns (-C) and endocrowns (-E) were produced (n = 10) using CAD-CAM technology, through scanning (CEREC Primescan, Dentsply Sirona) and milling (CEREC MC XL, Dentsply Sirona), and then adhesively bonded to fiberglass-reinforced epoxy resin. Computed microtomography was used to assess the marginal and internal gap and interfacial volume. A cyclic fatigue test (20 Hz, initial load = 100 N/5,000 cycles; step-size = 50 N/10,000 cycles until 1,500 N, if specimens survived, the step-size = 100 N/10,000 cycles until failure) was performed. Topography, finite element analysis (FEA), and fractography were also executed.Two-way analysis of variance and Tukey's post hoc tests were employed (α = 0.05) for marginal and internal gap and interfacial volume. Survival analysis based on Kaplan–Meier and Mantel–Cox tests (α = 0.05) was used for fatigue data.RC crowns demonstrated the smallest marginal gap, LD crowns the largest. Endocrowns presented intermediary marginal gap values. Internal gaps were all above the planned 120 µm space. The lowest gap was seen at the cervical-axial angle at crowns, regardless of material. At the axio-occlusal angle, LD crowns presented a lower gap than RC; meanwhile, there was no difference among endocrowns. When comparing occlusal/pulpal space, LD crowns showed the lowest values, and RC-C, LD-E, and RC-E were statistically similar. Fatigue testing revealed superior behavior for RC restorations, withstanding higher loads and more cycles before failure compared to LD. FEA indicated that the crowns required higher stress concentration to unleash their failure than endocrowns. Fractographic features confirm failure origin at surface defects located at the restoration/cement intaglio surface, where it concentrated the highest maximum principal stress.RC crowns and endocrowns presented lower marginal gaps than LD ones. Differences in other internal gap outcomes exist but within a nonclinically relevant threshold. The restoration fatigue behavior was influenced by the CAD-CAM material, but not by its design.
Keywords: ceramics; composite resins; dental marginal adaptation; mechanical tests; finite element analysis